Machine vision method for non-contact measurement of surface roughness of a rotating workpiece. Issue 1 (19th January 2015) - Kumar, B. M.; Ratnam, M. M.
Abstract : Purpose: – This paper aims to propose a non-contact method using machine vision for measuring the surface roughness of a rotating workpiece at speeds of up to 4, 000 rpm. Design/methodology/approach: – A commercial digital single-lens-reflex camera with high shutter speed and backlight was used to capture a silhouette of the rotating workpiece profile. The roughness profile was extracted at sub-pixel accuracy from the captured images using the moment invariant method of edge detection. The average (Ra), root-mean square (Rq) and peak-to-valley (Rt) roughness parameters were measured for ten different specimens at spindle speeds of up to 4, 000 rpm. The roughness values measured using the proposed machine vision system were verified using the stylus profilometer. Findings: – The roughness values measured using the proposed method show high correlation (up to 0.997 for Ra) with those determined using the profilometer. The mean differences in Ra, Rq and Rt between the two methods were only 4.66, 3.29 and 3.70 per cent, respectively. Practical implications: – The proposed method has significant potential for application in the in-process roughness measurement and tool condition monitoring from workpiece profile signature during turning, thus, obviating the need to stop the machine. Originality/value: – The machine vision method combined with sub-pixel edge detection has not been applied to measure the roughness of a rotating workpiece.